Air-conditioning system (building services) / Muhamad Luqman Hakim Ishak - Ishak, Muhamad Luqman Hakim (Universiti Teknologi Mara, Perak, 2017)
In every building in this world must have a building services, building services is a system which is control all the electrical service in the building. Function of this services is first to make sure the occupant of the building is safe which is for safety. Start from the lighting every building should have a daylight or natural lighting and artificial lighting which is the main point for building user. Then escalator and lift, for a high rise building or large building this type of transportation system should be installed. This feature will fulfill all the requirement need by Laws. All this services is providing to give comfort to all users.